PROBLEMS IN THE HYDRAULIC SYSTEMS OF HEAVY TRUCKS IN MINING OPERATIONS - Sharipov Alisher Kalbayevich (TADQIQOTLAR.UZ, 2024)
This paper explores the critical issues faced by hydraulic systems in heavy trucks used in mining operations. It discusses common problems such as hydraulic fluid leaks, contamination, overheating, and pump or valve failures, emphasizing their impact on truck  performance,  safety,  and  overall  operational  efficiency  in  harsh  mining environments.  The  paper  highlights  how  environmental  factors  like  dust,  extreme temperatures, and heavy loads exacerbate these issues, leading to increased downtime and  maintenance  costs.  It  also  provides  practical  solutions,  such  as  regular  system maintenance,  improved  filtration,  effective  cooling,  and  better  operator  training,  to mitigate  these  problems  and  enhance  system  reliability.  Ultimately,  the  paper underscores  the  importance  of  addressing  hydraulic  system  failures  to  maintain productivity and reduce the risks  associated with equipment  breakdowns in  mining operations.